2021
DOI: 10.3389/fcell.2021.678524
|View full text |Cite
|
Sign up to set email alerts
|

The Genomic Response to TGF-β1 Dictates Failed Repair and Progression of Fibrotic Disease in the Obstructed Kidney

Abstract: Tubulointerstitial fibrosis is a common and diagnostic hallmark of a spectrum of chronic renal disorders. While the etiology varies as to the causative nature of the underlying pathology, persistent TGF-β1 signaling drives the relentless progression of renal fibrotic disease. TGF-β1 orchestrates the multifaceted program of kidney fibrogenesis involving proximal tubular dysfunction, failed epithelial recovery or re-differentiation, capillary collapse and subsequent interstitial fibrosis eventually leading to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 291 publications
0
9
0
Order By: Relevance
“…TAZ is required for maximal TGF-β1-mediated expression of the SMAD target gene encoding plasminogen activator inhibitor-1 (PAI-1), a potent profibrotic clade E member of the serine protease inhibitor family (SERPINE1) [ 27 , 28 , 29 , 30 ], and a similar involvement of YAP in TGF-β1-induced PAI-1 expression is evident in lung tumor cells [ 31 ]. KEGG analysis confirmed, moreover, that convergence of the TGF-β and Hippo signaling pathways regulates transcription of the fibrosis-inducing connective tissue growth factor (CTGF; CCN2) and SERPINE1 genes [ 32 ] ( Figure 1 ). YAP knockdown effectively reduces levels of both CCN2 and PAI-1 (SERPINE1), while introduction of the constitutively active YAP S127A construct increases PAI-1 expression in immortalized cell lines [ 33 ].…”
Section: Cancer-associated Fibroblasts: Biology Of the Fibrotic Tumor...mentioning
confidence: 94%
See 1 more Smart Citation
“…TAZ is required for maximal TGF-β1-mediated expression of the SMAD target gene encoding plasminogen activator inhibitor-1 (PAI-1), a potent profibrotic clade E member of the serine protease inhibitor family (SERPINE1) [ 27 , 28 , 29 , 30 ], and a similar involvement of YAP in TGF-β1-induced PAI-1 expression is evident in lung tumor cells [ 31 ]. KEGG analysis confirmed, moreover, that convergence of the TGF-β and Hippo signaling pathways regulates transcription of the fibrosis-inducing connective tissue growth factor (CTGF; CCN2) and SERPINE1 genes [ 32 ] ( Figure 1 ). YAP knockdown effectively reduces levels of both CCN2 and PAI-1 (SERPINE1), while introduction of the constitutively active YAP S127A construct increases PAI-1 expression in immortalized cell lines [ 33 ].…”
Section: Cancer-associated Fibroblasts: Biology Of the Fibrotic Tumor...mentioning
confidence: 94%
“…Cytoscape profiling, moreover, similarly implicates SERPINE1 as a major core gene in the genomic program of tissue fibrosis, where it modulates focalized uPA/uPAR-dependent pericellular proteolysis and functions as a signaling activator for LRP1. String Protein– Protein Interaction Network and Gene Ontology analyses confirmed the cooperative role of SERPINE1 and TGF-β1 in the global process of normal and maladaptive (fibrotic) repair; both significantly contribute to the desmoplastic reaction and subsequent enhanced tissue stiffness [ 32 ]. This stromal barrier, and the associated increase in interstitial fluid, attenuates the effective delivery of chemotherapeutics to the TME (e.g., [ 7 , 191 ]).…”
Section: Caf-derived Pai-1 As a Poor Prognosis Biomarkermentioning
confidence: 99%
“…These results were also consistent with the 1,080 cm −1 lipid band. p53 is a particularly prominent transcriptional coregulator of TGF-β1 fibrosis response genes ( Higgins et al, 2021 ). The expression of p53 was especially marked in the CWP-3M group ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Suppression of YAP/TAZ activation by BU may be of particular importance because YAP/TAZ has been shown to sense ECM stiffness and to promote ECM production in a self-sustaining feedforward loop [ 34 ]. Interestingly, it was very recently shown that PAI-1 protein expression is mainly determined by the YAP/TAZ signaling pathway [ 35 ]. Therefore, the reduction of PAI-1 protein expression shown with butyrate in the present study confirms the predicted observed reduction in the Hippo signaling pathway (YAP/TAZ signaling) on the protein level.…”
Section: Discussionmentioning
confidence: 99%